2019
DOI: 10.1111/ejh.13234
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline‐induced cardiotoxicity in diffuse large B‐cell lymphoma: NT‐proBNP and cardiovascular score for risk stratification

Abstract: Objective:To evaluate the role of N-terminal pro-brain-type natriuretic peptide (NT-proBNP) and a cardiovascular (CV) risk score named FRESCO for predicting anthracycline-induced cardiotoxicity (AIC) in diffuse large B-cell lymphoma (DLBCL). Methods:A total of 130 consecutive DLBCL patients treated in first-line with anthracycline-containing immunochemotherapy. Competitive risk between NT-proBNP, FRESCO, and time to AIC was considered.Results: Cumulative incidence of AIC was 12.2% and 17.5% at 1 and 5 years, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
1
11
0
3
Order By: Relevance
“…In this study, we report a high incidence of emerging CVD, where almost one fourth (23.2%) of DLBCL patients receiving immunochemotherapy develop CVD. Previous studies show an incidence of emerging heart toxicity of 10-20% for AC or DXR treated cancer and lymphoma patients [17,18,21,[40][41][42][43]. Our result of 15.9%, with a quite long follow up time, fits into these results, despite the fact that our cases were clinically evident disease, whereas in some studies cases of silent heart failure only observed in ultrasound measurements were also included [21,40,41].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, we report a high incidence of emerging CVD, where almost one fourth (23.2%) of DLBCL patients receiving immunochemotherapy develop CVD. Previous studies show an incidence of emerging heart toxicity of 10-20% for AC or DXR treated cancer and lymphoma patients [17,18,21,[40][41][42][43]. Our result of 15.9%, with a quite long follow up time, fits into these results, despite the fact that our cases were clinically evident disease, whereas in some studies cases of silent heart failure only observed in ultrasound measurements were also included [21,40,41].…”
Section: Discussionsupporting
confidence: 79%
“…In DXR treated malignancies, some studies point at the possibility of using Troponin I as a predictor for heart failure, but find little evidence of the usefulness of NT-proBNP [17][18][19][20]. Contradictory to this, NT-proBNP improves the prediction of DXR induced cardiotoxicity when used in combination with a clinical risk score assessment function (FRESCO) in DLBCL [21].…”
Section: Introductionmentioning
confidence: 99%
“…Ferraro et al suggested 600 pg/ml as the cutoff value. They showed that patients with the NT-proBNP level of more than 600 pg/ml had 3.97 times higher risk of cardiac toxicity [ 43 ]. NT-proBNP elevation may stem from other reasons more than cardiac toxicity such as altered cardiac loading conditions and invalidate the use of NT-proBNP for detection of cardiac toxicity [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…With anthracycline chemotherapy playing a prominent role in lymphoma treatment, DLBCL patients' prognoses continue to improve because of earlier detection and newer targeted therapeutic drugs. With longer survivorship, there will be a large number of DLBCL patients who will have to face the risk of cardiovascular morbidity and mortality which caused by long-term toxicity of anthracycline chemotherapy [25][26][27][28]. Cardiotoxicity caused by anthracycline is often progressive and irreversible, which The QTc interval on the electrocardiogram (ECG) refers to the QT interval corrected according to heart rate or RR interval [32].…”
Section: Discussionmentioning
confidence: 99%